Fronteiras da Conversão: Histórias Indígenas Conectadas na América Equinocial do Século XVII - SANTOS, Nivaldo Germano dos (2023)
This work deals with the different roles played by the Indians in the face of missionary activity and the “Portuguese expansion” along the Equator during the 17th century. By analyzing the documentation of the Overseas Historical Archive (Resgate Project) and the colonial chronicles referring to the region, it was possible to understand some aspects of missionary activity (Jesuit and Franciscan) against some ethnic groups (Uruati and Cacai on the Itapecuru River; Aruã on Joanes Island), in order to rethink their impacts on native populations and understand indigenous agencies as the main aspect of this history of missions. In theoretical-methodological terms, in addition to post-colonial studies, connected histories were chosen and the contradictions of colonial discourse were explored, which favored understanding the historical possibilities to which Indians, missionaries and rulers were subject; and which provided an opportunity to balance the widely recorded Portuguese view of the process with the poorly documented indigenous perspectives and agencies. Thus, the aim is to reassess the history of the “Portuguese expansion”, carried out partially by missionary activity in Maranhão and Grão-Pará at that time. These listed meanings compromise the triumphant expansionist logic invented by the Portuguese and repeated by historiography and give special importance to the Indians in that historical process, considered in its plurality.